Structural and functional analysis of UGT92G6 suggests an evolutionary link between mono- and disaccharide glycoside-forming transferases - Huang, Fong-Chin; Giri, Ashok; Daniilidis, Melina; Sun, Guangxin; Härtl, Katja; Hoffmann, Thomas; Schwab, Wilfried (Plant and Cell Physiology, 2018)
Glycosylation mediated by UDP-dependent glycosyltransferase (UGT) is one of the most common reactions for the biosynthesis of small molecule glycosides. As glycosides have various biological roles, we characterized UGT genes from grapevine (Vitis vinifera). In silico analysis of VvUGT genes that were highly expressed in leaves identified UGT92G6 which showed sequence similarity to both monosaccharide and disaccharide glucoside-forming transferases. The recombinant UGT92G6 glucosylated phenolics, among them caffeic acid, carvacrol, eugenol and raspberry ketone, and also accepted geranyl glucoside and citronellyl glucoside. Thus, UGT92G6 formed mono- and diglucosides in vitro from distinct compounds. The enzyme specificity constant Vmax/Km ratios indicated that UGT92G6 exhibited the highest specificity towards caffeic acid, producing almost equal amounts of the 3- and 4-O-glucoside. Transient overexpression of UGT92G6 in Nicotiana benthamiana leaves confirmed the production of caffeoyl glucoside; however, the level of geranyl diglucoside was not elevated upon overexpression of UGT92G6, even after co-expression of genes encoding geraniol synthase and geraniol UGT to provide sufficient precursor. Comparative sequence and 3-D structure analysis identified a sequence motif characteristic for monoglucoside-forming UGTs in UGT92G6, suggesting an evolutionary link between mono- and disaccharide glycoside UGTs. Thus, UGT92G6 functions as a mono- and diglucosyltransferase in vitro, but acts as a caffeoyl glucoside UGT in N. benthamiana.